The ring and the book - Browning, Robert, 1812-1889 (Floating Press, 2009)
Browning's dramatic poem The Ring and the Book narrates the trial of a Roman for the death of his wife and her parents. He suspected his wife of having an affair with a cleric. The man appeals his sentence, though unsuccessfully. The poem is narrated by many different voices, each adding their version of events to the whole in a series of monologues.